Polsko-niemieckie pogranicze w programach operacyjnych europejskiej współpracy transgranicznej = Polish-German borderland in the european cbc operational programmes - Flakowski, Jarosław; Sługocki, Waldemar (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The paper presents the progress of use of state funds allocated to the Polish-German borderland within the framework of Objective 3 of the European regional policy. It describes main priorities of three Operational Programmes of the European Territorial Cooperation, which are performed on the German side by Saxony, Brandenburg and Mecklenburg-Western Pomerania, and on the Polish side by the voivodships: Lower Silesian, Lubuskie and West Pomeranian.
Keywords: pogranicze polsko-niemieckie; współpraca regionalna; Europejski Fundusz Rozwoju Regionalnego